A Framework for the Fund's Issuance of Notes to the Official Sector. (Policy Papers; Policy Paper, 2009)
On July 1, 2009, the Executive Board of the International Monetary Fund discussed the Managing Director's proposal for a framework for issuing notes to the official sector. The framework approved by the Executive Board was adapted on the basis of these discussions, as reflected in supplement 2 of the paper. It enables members to invest in IMF paper under note purchase agreements approved by the Board, without any pre-specified limit on the cumulative amount committed under note purchase agreements. The actual issuance of notes will occur should the IMF need additional resources at the time of a loan disbursement to a member. The notes would have similar financial terms to the IMF's recent bilateral borrowing agreements.